The Effectiveness Of Poster Comment Method In Teaching Writing Recount Text - Muhammad Edy Thoyib; Harizatul Aziziyah (JEET, Journal of English Education and Technology, 2025)
Writing skill is very important in the current era, yet writing is one of the most challenging skills to master. Consequently, the Teacher should be innovative in teaching writing in the English learning process for their students. This research aims to find out the effectiveness of Poster Comment in increasing students" ability to write Recount text. The research method of this study uses a quasi-experimental design. The alternative hypothesis (H1) was accepted, and the null hypothesis (H0) was rejected. It indicates that the Poster Comment method applied in the Experimental class effectively increased students'" ability to write recount text. The Poster Comment method was more effective in teaching writing recount text in second grade than the conventional method (lecturing).